Pendidikan pranikah sebagai upaya pencegahan risiko reproduksi dan pendewasaan usia nikah: A scoping review - Yulinda, Dwi; Anggawijayanto, Erydani; Ekawati, Ekawati; Sunarsih, Tri; Astuti, Endah Puji; Shanti, Elvika Fit Ari (Holistik Jurnal Kesehatan, 2025)
Background: Early marriage remains a global challenge that negatively impacts reproductive health and the quality of human resources. In Indonesia, the high rate of child marriage is an obstacle to achieving superior, healthy, and competitive human resources. Purpose: To examine premarital education as an effort to prevent reproductive risks and to promote maturity at marriageable age. Method: A systematic literature review using the Population, Concept, Context (PCC) framework was conducted. The literature was searched through databases such as PubMed and Google Scholar for articles relevant to premarital education and reproductive health from 2018–2025. Results: Of the eight studies analyzed, premarital education was proven effective in increasing brides' knowledge about reproductive health, nutrition, and marriage readiness. Interventions included classes at religious affairs offices, school education, community seminars, and participatory models such as FOCUS–PDCA. Key barriers included cultural resistance, limited facilitators, and lack of contextual materials. Conversely, policy support, collaborative approaches, and interactive educational methods were important supporting factors. Conclusion: Premarital education has significant potential to reduce early marriage rates and improve the reproductive readiness of young couples. Adaptive implementation, based on local culture, and integrated with behavior change communication strategies, is essential for long-term effectiveness. Suggestion: Premarital education can be developed in a more adaptive and contextual manner by integrating participatory approaches, based on local culture, and easily accessible digital media. The program needs to be strengthened with behavior change communication strategies so that increased knowledge leads to changes in attitudes and actions.   Keywords: Early Marriage; Premarital Education; Reproductive Health.   Pendahuluan: Perkawinan usia dini masih menjadi tantangan global yang berdampak negatif terhadap kesehatan reproduksi dan kualitas sumber daya manusia. Di Indonesia, tingginya angka pernikahan anak menjadi salah satu hambatan dalam mencapai pembangunan SDM unggul, sehat, dan berdaya saing. Tujuan: Untuk mengkaji pendidikan pranikah sebagai upaya pencegahan risiko reproduksi dan pendewasaan usia nikah. Metode: Penelitian literatur sistematis dengan pendekatan scoping review, menggunakan kerangka kerja PCC (Population, Concept, Context). Literatur dicari melalui database seperti PubMed dan Google Scholar untuk artikel tahun 2018–2025 yang relevan dengan pendidikan pranikah dan kesehatan reproduksi. Hasil: Dari 8 studi yang dianalisis, pendidikan pranikah terbukti efektif meningkatkan pengetahuan calon pengantin tentang kesehatan reproduksi, gizi, dan kesiapan pernikahan. Intervensi dilakukan dalam bentuk kelas KUA, edukasi sekolah, seminar komunitas, hingga model partisipatif seperti FOCUS–PDCA. Hambatan utama mencakup resistensi budaya, keterbatasan fasilitator, dan materi kurang kontekstual. Sebaliknya, dukungan kebijakan, pendekatan kolaboratif, dan metode edukatif interaktif menjadi faktor pendukung penting. Simpulan: Pendidikan pranikah berpotensi besar dalam menurunkan angka pernikahan usia dini dan meningkatkan kesiapan reproduksi pasangan muda. Implementasi yang adaptif, berbasis budaya lokal, dan terintegrasi dengan strategi komunikasi perubahan perilaku sangat dibutuhkan untuk efektivitas jangka panjang. Saran: Pendidikan pranikah dapat dikembangkan secara lebih adaptif dan kontekstual dengan mengintegrasikan pendekatan partisipatif, berbasis budaya lokal, dan media digital yang mudah diakses. Program perlu diperkuat dengan strategi komunikasi perubahan perilaku agar peningkatan pengetahuan berlanjut pada perubahan sikap dan tindakan.   Kata Kunci: Kesehatan Reproduksi; Pendidikan Pranikah; Pernikahan Dini.